2020
DOI: 10.22207/jpam.14.4.27
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles Synthesis from New Record Aquatic Bacteria of Nile Tilapia and Evaluation of their Biological Activity

Abstract: The current study investigates the isolation identification of bioactive strain from fish collected from El-Burrllus region in Egypt. The objective of the current study is to identify and assess the biological profile of a new record strain in Egypt Bacillus maritimus. The molecular identification of the selected promising isolate and phylogenetic analysis confirmed the accurate identity of the isolate as Bacillus maritimus. The novelty of the present study was not due to only to the fact that the Bacillus mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Activation of NF-κB in the liver results in elevated levels of TNF-α, IL-1, and IL-6 expression. Marine organisms are a wealthy supply of anti-inflammatory, biologically bioactive lipids. , The current study confirmed the ability of GOE as a potent antioxidant and anti-inflammatory agent. It examined the bioactive secondary metabolite contents of polyphenolic compounds and fatty acids through an investigation for anti-inflammatory by inhibiting the manufacturing of NO, ACHI, (TNF-α) in LPS-induced lung mouse tissues .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Activation of NF-κB in the liver results in elevated levels of TNF-α, IL-1, and IL-6 expression. Marine organisms are a wealthy supply of anti-inflammatory, biologically bioactive lipids. , The current study confirmed the ability of GOE as a potent antioxidant and anti-inflammatory agent. It examined the bioactive secondary metabolite contents of polyphenolic compounds and fatty acids through an investigation for anti-inflammatory by inhibiting the manufacturing of NO, ACHI, (TNF-α) in LPS-induced lung mouse tissues .…”
Section: Discussionsupporting
confidence: 71%
“…Total phytochemical screening of GOE assessed different bioactive classes (phenolic, flavonoids, and carotenoids) according to Nabil-Adam et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nabil-Adam and Shreadah [197] reported the results for EDX which revealed the occurrence of carbon, oxygen, chlorine, sulfur, and sodium in addition to Ag. Yumei et al [198] reported the X-ray diffraction (XRD) pattern of the AgNPs to display four prominent peaks at 38.2, 44.3, 64.4, and 77.5 in the 2-theta range.…”
Section: Physicochemical Properties Of the Produced Agnpsmentioning
confidence: 99%
“…In the study by Nabil-Adam and Shreadah [197], the AgNP size was determined to be 19.66 to 26.96 nm. Manivasagan et al [196] synthesized AgNPs using a bioflocculant produced by a bacterial Streptomyces sp.…”
Section: Physicochemical Properties Of the Produced Agnpsmentioning
confidence: 99%